Constructivist Teaching in Primary Classes - Sharma, Santosh (THE PRIMARY TEACHER, 2008)
Most of us are products of traditional instruction. As learners, we were exposed to teacher centered instructions, fact based subject matter, and a steady diet of drill and practice. Teacher centered education, teaching by transmission and learning by rote memorisation are part of teachers’ personal histories and these practices persist in today’s classrooms. In traditional, teacher centered classrooms, individual desks face the front of the room, where the teacher occupies a privileged space of knowing authority. Students work individually on identical, skill based assignments to ensure uniformity of learning. In this environment, it is assumed that more quiet and orderly the classrooms are, more likely the learning tends to take place. In order to move away from this traditional classroom culture, teachers require critical reflection. Teachers must ask themselves, ‘Is my role to transmit authoritative knowledge which I learnt during my school days or to nurture independent thinkers? How can I nurture students as independent thinkers?' Teachers will have to struggle to develop well articulated rationale for instructional decisions. Shifting the centers of authority and activity from teacher to students required both effort and persistence. In the beginning, the teachers can be uncomfortable with their apparent lack of control as students engage in activities with peers. But with persistence, teachers will discover themselves as investigators/guides, trying to find out new instructional strategies and decisions.